A nano-microdosimetric characterization of a therapeutic carbon ion beam at CNAO. (May 2020) - Bortot, D.; Mazzucconi, D.; Pola, A.; Fazzi, A.; Pullia, M.; Savazzi, S.; Colautti, P.; Conte, V.; Agosteo, S.
Abstract: A nano-microdosimetric tissue-equivalent proportional counter (TEPC) capable of measuring microdosimetric spectra of ionizing radiation in the range 500–25 nm was designed, constructed and deeply characterized in order to fill the gap between nanodosimetry and experimental microdosimetry. This work describes the first microdosimetric characterization at nanometric level of a 195.2 MeV/u carbon ion beam available at CNAO (National Centre for Oncological Hadron Therapy). The detector was properly placed at different depths in PMMA phantom across the depth-dose profile of the primary beam for measuring microdosimetric distributions for different simulated site sizes down to 25 nm at different depths. The acquired spectra show that this TEPC is capable of reproducing the beam slowing down, showing a shift towards higher lineal energies as the primary particles slow-down. Moreover, the distributions at different simulated site sizes for the same depth are influenced by secondary electrons: smaller site size spectra exhibit a shift towards higher lineal energies as the site decreases, while this is not the case for more distal positions, where the edge of the spectra is almost independent of the simulated site size. Monte Carlo simulations performed with the FLUKA code show a good agreement with the experimental results obtained in the present paper. Highlights: A nano-microdosimetric avalanche-confinement TEPC for the simulation of nanometric sites. Microdosimetric characterization at nanometric level of 195.2 MeV/u carbon ion beam at CNAO. Comparison between experimental data and Monte Carlo simulations performed with FLUKA.